1923
DOI: 10.1021/ie50162a012
|View full text |Cite
|
Sign up to set email alerts
|

The Examination of Low-Temperature Coal Tars—I.

Abstract: In this paper the principal consideration has been the relative results that may be secured with flames produced from different gases, without consideration of how these data may influence the design of appliances. A number of manufacturers are already making use of this information and are making changes in their burners to secure higher effi-ciency, greater flexibility, and increased safety of operation. AcknowledgmentThe author wishes to express his appreciation for the advice and suggestions of Walter M. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1925
1925
1930
1930

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Data and Calculations-The data for a determination are taken in the following form: (1) Weight of phenol ( 2) Room temperature at start of experiment (3) Barometric pressure in millimeters of mercury (4) Vapor pressure of toluene in millimeters of mercury at room temperature (5) Pressure on gas in millimeters of mercury (6) Volume of gas at room temperature (7) Volume of gas reduced to 0°C. and 760 mm.…”
Section: Sodium Methodsmentioning
confidence: 99%
“…Data and Calculations-The data for a determination are taken in the following form: (1) Weight of phenol ( 2) Room temperature at start of experiment (3) Barometric pressure in millimeters of mercury (4) Vapor pressure of toluene in millimeters of mercury at room temperature (5) Pressure on gas in millimeters of mercury (6) Volume of gas at room temperature (7) Volume of gas reduced to 0°C. and 760 mm.…”
Section: Sodium Methodsmentioning
confidence: 99%
“…In the present study water vapor was carefully eliminated from the gas mixture, as its absorption by the sulfuric acid employed to remove the nitrogen peroxide would have inbond (26), it would be expected that if the two double bonds were separated by several carbon atoms both would become saturated. Moreover, the results depend upon the ratio of the amounts of oil and reagent used (20,66). It has been shown that a constant result can be obtained only when this ratio is kept constant (20).…”
mentioning
confidence: 99%